1999
DOI: 10.1002/(sici)1097-0290(19990120)62:2<166::aid-bit6>3.3.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Increasing extracellular matrix production in regenerating cartilage with intermittent physiological pressure

Abstract: Isolated equine chondrocytes, from juveniles and adults, were cultured in resorbable polyglycolic acid meshes for up to 5 weeks with semicontinuous feeding using a custom-made system to intermittently compress the regenerating tissue. Assays of the tissue constructs indicate that intermittent compression at 500 and 1000 psi (3.44 and 6.87 MPa, respectively) stimulated the production of extracellular matrix, enhancing the rate of de novo chondrogenesis. Constructs derived from juvenile cells contained concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…The presence of extracellular matrix, which influences the microenvironment of the cells, is not taken into account in this first implementation. Extracellular matrix deposition is a highly complex process, regulated by biochemical and biophysical signals, currently not yet comprehensively investigated (Carver and Heath 1999;Dimicco and Sah 2003). Earlier models generally included significant limitations in modeling extracellular matrix deposition.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of extracellular matrix, which influences the microenvironment of the cells, is not taken into account in this first implementation. Extracellular matrix deposition is a highly complex process, regulated by biochemical and biophysical signals, currently not yet comprehensively investigated (Carver and Heath 1999;Dimicco and Sah 2003). Earlier models generally included significant limitations in modeling extracellular matrix deposition.…”
Section: Discussionmentioning
confidence: 99%
“…7 Representative methylmethacrylate-embedded sections (6 μm thick), from the edges (a, c, e, g) and center (b, d, f, h) of loaded (a, b, e, f) and unloaded (c, d, g, h) constructs cultured at 5% O 2 and 21% O 2 for 34 days, stained with toluidine blue. Bar 1,000 μm (a, b, c, e, g), 200 μm (d, f, h) increasing pressure with regard to the synthesis of cartilagelike tissue (Toyoda et al 2003a,b;Carter et al 2004;Carver and Heath 1999). Furthermore, using finite element modeling, we have found that a confined compression system is necessary to achieve a significant pressure gradient within the highly permeable and elastic porous polyurethane scaffold during load application (Goerke et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, an increase in the expression of mRNA for aggrecan and type IIcollagen (Ikenoue et al 2003;Toyoda et al 2003), as well as an increase in 35 SO 4 and [ 3 H]proline incorporation (Parkkinen et al 1993;Hall et al 1991) were shown to occur in chondrocytes in response to the applied hydrostatic compression. In a study of the long-term adaptation to intermittent pressure, chondrocytes subjected to 360 daily pressurization cycles to 3.44 MPa or 6.87 MPa for 5 weeks accumulated approximately tenfold the amount of glycosaminoglycan as non-pressurized controls (Carver and Heath 1999a). There is less information available on the effect of hydrostatic pressure on mesenchymal stem cells, but it was recently reported that 1.0 Hz sinusoidal hydrostatic pressure of 5.03 MPa applied to human mesenchymal progenitor cell aggregates for 4 h/day for 7 days increased proteoglycan and collagen content (Angele et al 2003).…”
Section: Introductionmentioning
confidence: 99%